BOOSTING HUMAN CAPITAL: TRANSFORMING BOJONEGORO’S HUMAN RESOURSE CAPACITY THROUGH K3 CERTIFICATION AND BNSP COMPETENCY - Arya Raditya Pratama; Ana Kumalasari; Rupiarsieh Rupiarsieh (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
This study aims to analyse the impact of Occupational Health and Safety (OHS) training and certification on improving human resource capacity in Bojonegoro Regency. The main issue is the suboptimal utilisation of OHS training programmes in improving the competence and productivity of participants from the Department of Industry and Labour. The research is based on human capital theory, the Kirkpatrick evaluation model, and the ADKAR change model, which integrate a holistic approach to human resource development. The research method used an explanatory quantitative approach with primary data collection through questionnaires that had been tested for validity and reliability on 114 training participants using purposive sampling techniques, then analysed using descriptive analysis and simple linear regression with SPSS application. The results showed that most participants experienced a significant increase in knowledge, skills, attitudes, and motivation to apply OSH principles in the workplace. The validity, reliability, normality, and simple linear regression tests proved the effect of training on human resource capacity. The research recommendations emphasise that OSH training and certification are investment strategies that need to be continuously improved through sustainable curriculum development, sustainable evaluation mechanisms, and institutional support to ensure the transfer of knowledge to practice in the field.